2021
DOI: 10.3390/foods10050993
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum Phenolic Compounds Are Associated with Cell Growth Inhibition through Cell Cycle Arrest and Apoptosis in Human Hepatocarcinoma and Colorectal Adenocarcinoma Cells

Abstract: Phenolic compounds in some specialty sorghums have been associated with cancer prevention. However, direct evidence and the underlying mechanisms for this are mostly unknown. In this study, phenolics were extracted from 13 selected sorghum accessions with black pericarp while F10000 hybrid with white pericarp was used as a control, and cell growth inhibition was studied in hepatocarcinoma HepG2 and colorectal adenocarcinoma Caco-2 cells. Total phenolic contents of the 13 high phenolic grains, as determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of apigeninidin-rich S. bicolor extracts that elicit selectivity for a lung adenocarcinoma cell line (A549). Previous reports had reported anticancer effects against a wide range of cancer cells, including leukaemia (HL-60) 73 , breast cancer (MCF-7 and MDA-MB 231) 80 , 88 , cancer cell of the colon (HT-29) and liver (HepG2) 89 , 90 , malignant cells of colonocytes 91 and hepatoma (Hepa1c1c7) 92 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of apigeninidin-rich S. bicolor extracts that elicit selectivity for a lung adenocarcinoma cell line (A549). Previous reports had reported anticancer effects against a wide range of cancer cells, including leukaemia (HL-60) 73 , breast cancer (MCF-7 and MDA-MB 231) 80 , 88 , cancer cell of the colon (HT-29) and liver (HepG2) 89 , 90 , malignant cells of colonocytes 91 and hepatoma (Hepa1c1c7) 92 .…”
Section: Discussionmentioning
confidence: 99%
“…Human colorectal cancer Caco-2 cells and hepatocarcinoma HepG2 cells are two common cellular antioxidant activity testing models through MTT assay [7,15]. EC 50 values of sorghum varieties (i.e., Liberty, Mr-Buster, Cracka, IS131C, Shawaya Short Black 1) varied from 0.4 to 127.1 mg/mL, which assessed the total antioxidant effect of both extracellular and intracellular environments [15].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Studies have reported sorghum phenolic extracts possessthe antioxidant activity, phase II enzyme induction, regulation of p53 gene, anti-proliferative effect on cancer cells, and induction of cancer cell apoptosis [4,7,[46][47][48]. Quercetin, a flavonoid found in sorghum grain, has been reported to inhibit b-catenin signaling in SW480 colon cancer cells [49].…”
Section: Anti-proliferative Effectmentioning
confidence: 99%
See 2 more Smart Citations